Willingness to purchase counterfeit luxury brands: A cross‐cultural comparison. (2nd May 2021) - Tunçel, Niray
Abstract: This study examines the impact of idealism, possession‐based happiness, and the attitude toward the legality of counterfeits on the willingness to buy counterfeit luxury brands in Turkey and Slovenia. Data are collected from 205 consumers in Slovenia and 224 consumers in Turkey and analysed using Partial Least Square Structural Equation Modeling. The results confirm a negative impact of idealism on the attitude toward the legality of counterfeits and a positive impact of this attitude on the willingness to purchase counterfeit luxury brands. Turkish consumers show a positive effect of possession‐based happiness on the attitude toward counterfeits. The impact of idealism and possession‐based happiness on the willingness to purchase counterfeit luxury brands among Slovenian or Turkish consumers was not found. The study contributes to the literature by providing a cross‐cultural focus on specific personal antecedents, which the current literature has limited knowledge of and conflicting findings.